Directions of using Visual resources in teaching for a student specializing in art education teacher at the Hashemite University - Alghuwairi, Bayan Flaih (Journal of Educational and Psychological Sciences, 2021)
This study targeted to uncover the trends of using of visual sources in the teaching process, Art Education at the Hashemite University was devoted to and identify the effect of both gender and experience on visual sources. The sample consisted of field training students in the fourth year art education major in the College of Science Pedagogical Among the students of the Hashemite University for the academic year 2019/2020, and they were chosen in an intentional way and were developed to measure these trends and were of sufficient validity and stability for the purposes of this study, and the study tool was distributed to all students, as their number reached (583)Male and female students The study found the following results:The results of the study revealed positive trends for me Students, Towards the use of visual sources in a process Teaching, there were statistically significant differences attributed to sex and that in favor of females Where I got an arithmetic mean (3.49), while males got a mean (3.30), and the difference was statistically significant at the level of (α=0.05). While there were also statistically significant differences attributed to the experience in visual sources and equipment, in favor of the average experiences, as they got an arithmetic average (3.54), while the large experiences got an arithmetic average (3.53), and the few experiences got an arithmetic mean (3.41), and the difference was statistically significant at the level of (α=0.05).It yielded search results The researcher presented a number of recommendations About The use of visual sources in the teaching process.
Keywords: direction; Students of art education; Visual sources